Educational inclusion and the right to education: The senses in dispute - Sverdlick, Ingrid (Education Policy Analysis Archives, 2019)
This article discusses, from a historical perspective, the political dispute over the senses that the right to education and inclusive education have been in different models or educational proposals over time and its particular configuration in the today. It is an analysis that incorporates a look over power struggles that they occur in the field of discourse, understanding the senses that can have the words and the concepts associated with them, to occupy fields that are not only theoretical or speech fields, but they are also fields of political practice. On the other hand, this political reflection is complemented with a critical analysis of school educational inclusion practices, from seeing the results of a research that asked about the forms of appropriation of public policy in secondary schools with projects of educational inclusion of the province of Buenos Aires, Argentina between 2013 and 2015. We are particularly interested in the senses and tensions that assumes the educational inclusion in the discourses and practices of principals and teachers, as much as by the aspects of school life that limit and put in tension these conceptualizations, discourses and practices.